2003
DOI: 10.1080/13648470301268
|View full text |Cite
|
Sign up to set email alerts
|

Learning how to ask in ethnography and psychotherapy

Abstract: To social anthropologists an affinity with psychotherapy lies in the view that this discipline is a social science. Increasingly, social anthropologists offer comments and analyse their own data using psychotherapeutic or psychoanalytic frames of reference. At the same time, a methodological crisis has developed in ethnography. This is a crisis of how to carry out an ethnographic enquiry in a disciplined manner without either claiming to be a detached observer on the one hand or explaining away the subjective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…As noted earlier, research has indicated multiple dimensions to individual identity (Harris and Sims 2000). This study used circular questioning, common in family systems theory but only recently introduced to ethnographic interviewing (Krause 2003) to guide participants in exploring multiple contexts and dimensions of their racial and cultural identities. Solely to illustrate the type of interview data that this renders, this section presents a quote taken from one such interview.…”
Section: Collecting Relevant Datamentioning
confidence: 99%
“…As noted earlier, research has indicated multiple dimensions to individual identity (Harris and Sims 2000). This study used circular questioning, common in family systems theory but only recently introduced to ethnographic interviewing (Krause 2003) to guide participants in exploring multiple contexts and dimensions of their racial and cultural identities. Solely to illustrate the type of interview data that this renders, this section presents a quote taken from one such interview.…”
Section: Collecting Relevant Datamentioning
confidence: 99%
“…To date, the deployment of CA and DA for the study of family therapy remains a relatively marginal venture. This is perhaps striking if we consider Bateson's seminal research and his sound past in ethnography (Krause, 2003), the overall welcoming of qualitative research methodologies (Burck, 2005;Gilgun, 2005Gilgun, , 2012Singh, 2011), and the existence of "hybrid" attempts for a discursive analysis of family therapy sessions (Troemel-Ploetz, 1977;Watzlawick et al, 1967). On the other hand, the majority of the existing DA and CA studies of psychotherapy use transcribed family therapy sessions as their data (Avdi & Georgaca, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Our use of an open discussion format and an introductory open-ended question of the circular type may have contributed to the development of the new typology we have constructed of youngsters' understanding of their parents' care. While this format is commonly used in clinical family therapy, it is rare in qualitative illness research (11).…”
Section: Discussionmentioning
confidence: 99%
“…According to the participant's response to the first question more penetrating questions were then posed. The circular question format, asking one person about somebody else, was chosen to emphasize the purpose of the study (11). The more penetrating questions then delved further into these relationship issues rather than investigating the participant's experience of themselves, their illness and situation.…”
Section: Methodsmentioning
confidence: 99%